IMPLIKASI PENERAPAN IFRS 9 PADA DAYA PREDIKSI CKPN TERHADAP KERUGIAN KREDIT BANK - Elok Heniwati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
Changes in accounting standards affect the formation of loan loss provisions (LLP), which impacts bank reporting of actual credit losses. It is assumed that IFRS 9 with a forward-looking approach, produces a higher predictive power for LLP than it according to a backward-looking approach (IAS 39). This study compares the ability of LLP to predict bank actual credit losses between the periods of IAS 39 and IFRS 9. For this purpose, the study observes quarterly data of 3,022 data originating from a sample of banks in Indonesia (2,461) and Thailand (561) for the period IAS 39 (2018–2019) and IFRS 9 (2020–2021). This study applied some analyses, including the correlation and the general least squares method. The study results show that the predictive ability of PKP for the IFRS 9 period is higher than the IAS 39 period, which is consistent with the forward-looking ECL model. Furthermore, related to the interaction between standards and incentives, this study found that the predictive power of PKP regarding actual credit losses (KRG) in the IFRS 9 period was higher for banks with high-income levels but lower for large banks. The main limitation is that the study is a short period of IFRS 9 in both countries. The impact of implementing IFRS 9 can help regulators and associations of professional accountants in Indonesia and Thailand consider appropriate strategies to promote the application of IFRS 9. This research empirically observes the marginal impact of implementing IFRS 9 regarding forming loan loss reserves to predict KRG using data from ASEAN countries.